PEMENUHAN HAK TENAGA KERJA DALAM PENERIMAAN UPAH PEKERJA HARIAN LEPAS PADA(BBI) BALAI BENIH INDUKDI KECAMATAN RETEH KABUPATEN INDRAGIRI HILIR BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Hapsah, Siti; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Workers can not be denied existence in an intermediate working relationship theparent seed center with its workers, because they give each other a product plants that canbring benefits to the parent seed parent itselt. Meaning that the worker is a very importantfactor in a business activity carried out in the main breeding center. One of those cases doesnot fulfill the right of the worker daily freelancers who have the status of workers/laborees inacceptance of unfair wages in accordance with the legislation can be found in the main subdistrictseedlings reteh districts indragiri downstream, freelance worker less get welfareregarding the acceptance of unfair wages of 1.760.000 (one million seven hundred and sixtythousand rupiah ) per month that workers should earn 2.163.658 ( two million one hunfredsixty three thousand six hundred fifty eight rupiah ) per month.it appears that workers onlyearn wages that are still below the minimum wage, whereas based on government regulationnumber 78 year 2015 about wages in chapter 3 says that: wage policy is directed to theachievement of income that fulfills a decent living for the workers.The purpose of writing this thesis, nemely: to know how the fulfillment of the rights ofdaily workers freely in the receipt of wages at the parent seed center in the subdistrict ofindragiri downstream district. Second, to find out the cause of non-fulfillment the right ofdaily workers freelance in the receipt of wages at the main breeding center in the subdistrictof indragiri downstream regency.This type of research is a sociological study, because of the research on the effectiveness ofthe prevailing law.This researchwas conducted at the main breeding center in the subdistrictof indragiri downstream, while the population and sample were is a whole party related tothe problems studied in this study, data sources used, primary data,secondary data andtertiary data, techniques data collection in this study by interview and literature review.From the results of research problems there are two main things that can beconcluded. First, casual workers who work in the main breeding centers receive wages lessthan the minimum wage set by the downtream indragiri district. Second, the cause of wagesless than the minimum wage of indragiri downstream regencies is a system of less controlledand sanctioned sanctionss which is less run by the labor and transmigration offices of thedownstream indragiri district. The author’s suggestion, first, the casual worker must be madea written work contract in order for, the wage given in accordance with the minimum.Second, the labor and transmigration services must perfrom their functions as supervisionand protection for the workforce.Keywords : daily wage-worker fulfillment of parent stock